2010
DOI: 10.1111/j.1468-3083.2010.03639.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the dermatoscopic and histopathological features of pigmented basal cell carcinoma

Abstract: Dermatoscopy facilitates prediction of the corresponding histopathological findings in pigmented BCC, based on specific dermatoscopic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 21 publications
3
32
0
1
Order By: Relevance
“…As a reasonable consequence, different histopathologic subtypes display different dermoscopic patterns, as has been highlighted by recent d ermoscopic studies on BCC ( Figure 5) [1][2][3][4][5][6][7][8].…”
Section: Dermoscopy For Management Of Bccmentioning
confidence: 93%
See 3 more Smart Citations
“…As a reasonable consequence, different histopathologic subtypes display different dermoscopic patterns, as has been highlighted by recent d ermoscopic studies on BCC ( Figure 5) [1][2][3][4][5][6][7][8].…”
Section: Dermoscopy For Management Of Bccmentioning
confidence: 93%
“…The list of dermoscopic criteria of BCC has been several times updated and renewed, while their correlation to well-known histopathologic alterations of the disease has been demonstrated [1][2][3][4][5][6][7][8].…”
Section: • • Dermoscopic Criteria Of Bccmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Corresponding histopathologic findings can be predicted by means of dermatological examination in pigmented BCC. [14] Warshaw et al reported that the addition of dermatoscopic images to clinical images increased the diagnostic accuracy in teledermatologic evaluation of malignant non-melanocytic lesions. [15] Basal cell carcinoma BCC is the most common type of skin cancer in humans.…”
Section: Introductionmentioning
confidence: 99%